Selected Vegetables and Spices Improve DNA Quality and Histopathological Abnormalities in Roof Rats (Rattus rattus) Exposed to Cement Dust - Yahaya, Tajudeen Olanrewaju; Salisu, Titilola; Musa, Mohammed; Izuafa, Abdulrazaq; Obi, Chidiebere; Ribah, Samuel; Abubakar, Suleiman (Folia Medica Indonesiana, 2023)
Highlights: 1. This study identified feasible and affordable alternatives to ineffective conventional cement production pollution control strategies. 2.M. oleifera, H. sabdariffa, T. occidentalis, and Z. officinale are effective as personal interventions to ameliorate the effects of cement pollution. Abstract Conventional pollution control strategies in the cement industry have proven ineffective. As a result, effective and targeted complementary interventions are necessary. This study used roof rats (Rattus rattus) inhabiting the premises of a cement plant in Sagamu, Ogun State, Nigeria, to evaluate the ameliorative effects of moringa (Moringa oleifera), roselle (Hibiscus sabdariffa), fluted pumpkin (Telfairia occidentalis), and ginger (Zingiber officinale) on cement dust exposure. A total of 42 rats were divided into seven groups, with each group consisting of six rats. Group 1 served as the negative control group and was not exposed to any substances, while group 2 served as the positive control group and received standard feed throughout the experiment. Meanwhile, groups 3, 4, 5, 6, and 7 served as the experimental group. Rats in these groups were fed with 400 mg/kg of ethanolic extracts of Z. officinale, M. oleifera, T. occidentalis, H. sabdariffa, and a mixture of the four extracts with a composition of 1:1:1:1, respectively, for 90 days. The plasma DNA concentrations, DNA purity, and lungs of the rats were examined before and after the experiment. Prior to the experiment, the exposed rats had higher plasma DNA concentrations and lower DNA purity, as well as severe fibrosis and congested alveoli in their lungs, compared to the unexposed rats. At the end of the experiment, the experimental groups showed a significant increase in DNA purity (pâ‰¤0.05) and a decline in plasma DNA concentrations compared to the positive control group. In addition, the experimental groups showed fewer histopathological abnormalities than the positive control group. The mixture of the extracts yielded the most favorable results, followed by the extracts of Z. officinale, M. oleifera, T. occidentalis, and H. sabdariffa, respectively. These findings suggested that the selected vegetables and spices have the properties to ameliorate the effects of cement dust exposure. Therefore, individuals residing in close proximity to cement plants are encouraged to consume these vegetables and spices.